Money and banking in the UK : a history - Collins, Michael (London ; New York : Croom Helm, 1988)
This is a highly competent, well organized, clearly written, intelligible, and intelligent textbook, covering the history of the U.K. banking system -from 1826 to 1985. It effectively fills a large gap in the literature.
Includes index.
Includes bibliographical references: p. 593-626.
rpm 03/05/2018
Loans
Keywords: Banks and banking; Monetary policy; Money; Great Britain